The role of the annulment action in protecting the principle of legality in the Algerian legal system - OUASLI, Mohamed; LALAOUNA, Souleyman (Art Law and Accounting Reporter, 2026)
The principle of legality constitutes one of the foundational pillars upon which the rule-of-law state is built. It requires that the administration, in all its acts and operations, be subject to the provisions of law, thereby ensuring the protection of individual rights and freedoms and preventing the abuse of public authority. This principle draws its strength from a range of written sources, including the constitution, legislation, and regulatory decrees, as well as unwritten sources represented by custom, the general principles of law, and judicial precedent, all of which contribute to entrenching respect for the law and achieving a balance between the public interest and individual rights. The annulment action emerges as the most important judicial mechanism safeguarding the principle of legality, as it is the action brought by individuals before the administrative courts to challenge unlawful administrative decisions and seek their annulment. This action is distinguished by being an objective, in rem judicial action directed against the administrative decision itself, aimed at protecting legality and the supremacy of law. It is also one of the actions falling within the jurisdiction of the administrative judiciary, through which the administrative judge exercises effective oversight over the administration’s acts. To ensure its admissibility, the legislator requires the fulfillment of conditions relating to standing (capacity), interest, time limits, and the challenge of a final administrative decision.